Exclusive transabdominal trans-amniotic approach for chorionic villus sampling in posterior placenta: a novel approach for prenatal diagnosis of genetic disorders - Patel, B. I.; Patel, Saumil; Patel, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of the study was to evaluate role and safety of transabdominal trans-amniotic approach for Chorionic villus sampling (CVS) for prenatal diagnosis of genetic disorders. Methods: Retrospective analytical study carried out on data form couples coming for pre-natal diagnosis from January 2010 to February 2021. Patient related parameters like age, gestational age; procedure related parameters like amount of sample, number of attempts required; different genetic disorder diagnosed and complications by both the approaches of CVS were recorded and analyzed. Results: Total 2287 patients undergoing CVS with mean age of 27±3.3 years were included. Majority (1621;70.9%) had CVS procedure at gestational age of 12-14 weeks. On analyzing physician’s perception, 663 (29%) patients having complete posterior placenta could not be accessible with routine trans-abdominal CVS and opted for trans-amniotic approach. Amount of sample yield and number of attempts were not statistically significant (p>0.05) by both methods of CVS. Thalassemia major was found in 948 (41.45%) followed by thalassemia minor in 525 (22.96%) patients. No statistically significant difference was found for developing complications by both the methods (p>0.05). Most common complication was pain and discomfort which was relieved by simple analgesics. Out of total 17 (0.74%) abortions; 13 (0.80%) from routine transabdominal and 4 (0.60%) from trans-amniotic route CVS with no statistically significant difference among them (p>0.05). No case of post procedure infection was observed. Conclusions: In complete posterior placenta CVS procedures usually postponed by most physicians leading to delay in diagnosis of genetic disorders. The novel method transabdominal trans-amniotic approach for CVS is effective and safe in skilled hands and can help in early prenatal diagnosis of genetic disorders.